Choline acetyltransferase and acetylcholine levels in Drosophila melanogaster: a study using two temperature-sensitive mutants - Salvaterra, PM (J Neurosci, 1985)
Choline acetyltransferase (ChAT, acetyl-CoA-choline-O- acetyltransferase, EC 2.3.1.6) activity was measured in homogenates prepared from wild type (Canton S) and two temperature-sensitive presumed ChAT structural gene mutants (Chats1 and Chats2; originally described by Greenspan, R. (1980) J. Comp. Physiol. 137: 83–92) of Drosophila melanogaster. Wild type flies grown at 32 degrees C for 12 or 24 hr showed increased ChAT activity, whereas Chats1 and Chats2 flies showed a progressive decrease in enzyme activity at 32 degrees C (restrictive temperature) when compared to flies reared at 18 degrees C (permissive temperature). Acetylcholine (ACh) and choline levels were determined in formic acid-acetone extracts of individual fly heads, and the ACh levels showed the same variation with time at 32 degrees C as did the ChAT activity. In contrast, choline levels did not vary in any regular pattern. Acetylcholinesterase (EC 3.1.1.7) activity did not vary during heat treatment (except for Chatts2 flies held at 32 degrees C for 24 hr, where a decrease was observed) indicating that this treatment may be specific for ChAT. We conclude that ChAT activity is strongly correlated with ACh levels in Drosophila heads and may thus have an important regulatory role in determining the levels of ACh available for physiological function. We also report on the preliminary characterization of ChAT in both Chats mutants and compare the biochemical properties to those of wild type enzyme. Isoelectric focusing profiles of ChAT from both Chats mutants revealed enzymes with altered patterns compared to wild type, indicating that the mutations are most probably in the structural gene.